OP0153-HPR HOW CAN WE HELP PEOPLE WITH FIBROMYALGIA? NO EFFECTS OF AN EVIDENCE-BASED MULTICOMPONENT REHABILITATION PROGRAMME. (2nd June 2020) - Zangi, H. A.; Haugmark, T.; Provan, S. A.; Smedslund, G.; Hagen, K. B.
Abstract : Background: Patients with fibromyalgia (FM) suffer from high symptom burden, lack of understanding and few available treatments. EULAR evidence-based recommendations for the management of FM state that optimal management should focus on prompt diagnosis, patient education and initially non-pharmacological treatments 1 . Physical exercise is recommended for all patients and may be combined with tailored psychological therapies for those with unhelpful coping strategies. The evidence for these combined therapies is still weak and further studies are warranted. A Norwegian mindfulness- and acceptance-based intervention, the Vitality Training Programme (VTP), has shown beneficial effects in groups of patients with rheumatic and musculoskeletal diseases 2, 3, but has previously not been tested in combination with physical exercise. Objectives: To test the effects of a multicomponent rehabilitation programme comprising the VTP followed by supervised physical exercise for patients with recently diagnosed FM. Methods: Patients with widespread pain ≥3 months; aged 20 to 50, who were working or had not been out of work >2 years, were referred to rheumatologists for diagnosis clarification according to ACR 2010 FM diagnosis criteria. All eligible patients participated in a 3-hour group-based patient education programme before inclusion and randomization. The intervention group received the VTP, a 10-session group programme followed by 12 weeks supervised physical exercise. The control group followed treatment as usual. Self-reported data were collected electronically. Primary outcome was Patient Global Impression of Change (PGIC), scored as 1= much worse, through 4=no change, to 7=much better, measured at 12 months follow-up. Values 6 - 7 were considered clinically relevant improvement. Secondary outcomes were pain, fatigue, sleep quality, psychological distress, mindfulness, physical activity, motivation and barriers for physical activity and work impairment. Effects were analysed by Analysis of Covariance (ANCOVA). Results: 170 patients were randomised, 85 to intervention and 85 to control. There were no statistically significant differences between groups in PGIC at 12 months; 13% in the intervention group and 8% in the control group reported clinically relevant improvement (Figure 1 ). No statistically significant between-group differences were found in pain (p=0.05), fatigue (p=0.72), sleep quality (p=0.52), psychological distress (p=0.34), physical activity (p=0.78) or work impairment (0.27). There were significant between-group differences in patients' tendency to be mindful (p=0.02) and 'perceived benefits of exercise' (p=0.03), in favour of the intervention group. Conclusion: At 12 months follow-up, a multicomponent rehabilitation programme had no significant health effects compared to treatment as usual. The results differ from previous studies on the VTP in patients with inflammatory joint diseases. The question, how can we help people with FM, remains unresolved. References: [1]Macfarlane GJ et al. EULAR revised recommendations for the management of fibromyalgia. Ann Rheum Dis 2017;76:318-28 [2]Zangi HA et al. A mindfulness-based group intervention to reduce psychological distress and fatigue in patients with inflammatory rheumatic joint diseases: a randomised controlled trial. Ann Rheum Dis 2012;71:911-17 [3]Haugli L et al. Learning to have less pain - is it possible? A one-year follow-up study of the effects of a personal construct group learning programme on patients with chronic musculoskeletal pain. Patient Educ Couns 2001;45:111-18 Acknowledgments: The SALSA project group Disclosure of Interests: None declared